Critical discourse analysis of Covid-19 vaccine news in the English and Arabic media - Alqaysi, Fouad Hussein Ali; Manjet Kaur Mehar Singh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The virus takes a toll on people worldwide regarding the economy and social life, control the spread of this virus and taking the vaccine are most problems faced by the governments. This article examines the news coverage of the Coronavirus vaccine, focusing on the Covid-19 vaccine and how it has been exploited politically and ideologically in the English and Arabic media (BBC and Al-Jazeera). Since there are limited researches of CDA on the vaccine discourse in the media (how the vaccine is portrayed), this study aims to contribute to the researches in CDA about Covid-19 vaccine discourse. Fairclough's (1995) three-dimensional critical discourse analysis was utilised as a foundational framework to investigate the amount to which power is linguistically expressed persuasively in every discourse of different media genres using particular lexical, rhetorical, and pragmatic methods. A qualitative approach was used to analyse the selected data (two discourses from each media type). The findings revealed that the governments, through media, had used linguistic features to persuade people's minds, convincing them to take the vaccine as the only solution. The ethical appeal, cultural, societal and religious is very well generated in the discourse of both media genres.